ANALISIS BAURAN PEMASARAN TERHADAP PELAKU USAHA MIKRO DI DESA TEGALSARI KARAWANG - Destya Hardyka Putri; Rachman Hadi; Alamsah Alamsah; Nurminingsih Nurminingsih (Sekolah Tinggi Pariwisata Mataram, 2022)
This article was created with the aim to determine and analyze marketing strategies undertaken by businesses in Tegalsari Village. The research method used in the form of SWOT analysis and descriptive analysis method using quantitative research approach. Quantitative descriptive analysis is the analysis of data that is not in the form of numbers, but in the form of a series of information extracted from the results of the study. Therefore, the author must first know how the state of the village as well as internal and external factors that affect the existing marketing strategy in tegalsari village and also some possible alternative strategies by using strengths to take advantage of opportunities to overcome weaknesses, avoid threats and minimize weaknesses and avoid threats. Data collection techniques conducted by researchers is to conduct interviews and direct observation in Tegalsari Village. In addition, there are additional supporting data from reading books and other sources related to the title of the study. The Data obtained from the data collection is then analyzed using SWOT analysis to determine what are the strengths, weaknesses, opportunities, and threats of marketing strategies undertaken by businesses in Tegalsari Village. The results shown by interviews with business actors that aggressive business actors with a very favorable situation for business actors themselves. Where, businesses have the power so that they can take advantage of existing opportunities by utilizing the support of the Trade Office to more broadly enter the market share, maximize promotion, online or offline media, always read the market share every time, prioritize consumer satisfaction with product quality, multiply trade ideas and affordable prices and find strategic locations to facilitate consumers.